Establishing the Operational Practices Of E-Learning In An Online And Distance Learning Curriculum In Botswana: A Case Study Of An Open University - Magetse, Tebogo Angela; Khoza, Samuel Dumazi (Research in Social Sciences and Technology, 2026)
This qualitative study established the students’, tutors’, and Learning Management officers’ practices of e-learning in an Online and Distance Learning curriculum in Botswana. An adjunct model was used as an underpinning model where seven students who were registered for an online programme, together with two of their LMS officers and tutors, were purposively selected to take part in the study. Open-ended e-questionnaires were used as interviews where the participants had a chance to share with the authors their operational practices with e-learning. The reason for e-questionnaires was prompted by the fact that the data was collected during the COVID-19 outbreak. Findings revealed that the online University in Botswana has a clear plan for online programmes, but students continue to struggle with it due to various reasons like lack of internet connectivity, poor maintenance of gadgets, as well as age, which makes most of them not digital natives. Tutors showed dissatisfaction with how students engage with them online, where due dates are missed, while the LMS officers felt like they do not have proper support from the institutions in terms of resourcing them to assist struggling students. The study recommends that perhaps the government needs to come in to improve on issues of infrastructure in the country, where the internet and bandwidth would be improved for e-learning to thrive.